Polyisocyanate composition, resin composition, resin cured product, resin cured film, sticky resin composition, and surface protective film

The polyisocyanate composition, with its specific molecular structure and functional groups, addresses the need for a surface protective film that tracks well on curved surfaces, dries quickly, peels easily, and minimizes adhesive contamination, achieving enhanced performance in adhesiveness and durability.

JP2025040950APending Publication Date: 2025-03-25ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024150568
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-12
Filing Date
2024-09-02
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

There is a demand for an adhesive composition that provides a surface protective film with better tracking on curved surfaces and unevenness, quick drying, easy peeling, and reduced contamination of the adhesive during peeling.

Method used

A polyisocyanate composition derived from di(tri)isocyanates and polyols, with specific molecular weight and functional group ratios, containing isocyanurate groups, allophanate, and urethane groups, is used to create a resin composition that forms a surface protective film with improved adhesiveness, peelability, and reduced contamination.

Benefits of technology

The polyisocyanate composition achieves excellent quick-drying properties, hardness, and strength in the cured resin product, along with improved adhesiveness and peelability of the surface protective film, reducing contamination during peeling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025040950000001
    Figure 2025040950000001
  • Figure 2025040950000002
    Figure 2025040950000002
  • Figure 2025040950000003
    Figure 2025040950000003
Patent Text Reader

Abstract

To provide a polyisocyanate composition, when processing into a surface protective film, good in pasting property and peelability, improved in staining property by an adhesive when peeling, a resin composition, a resin cured product, a resin cured film, a sticky resin composition, and a surface protective film.SOLUTION: A polyisocyanate composition includes: a polyisocyanate derived from at least one di(tri)isocyanate (b1) selected from the group consisting of an aliphatic di(tri)isocyanate and an alicyclic di(tri)isocyanate, and a bi- or more functional polyol (b2) having a number average molecular weight of 250 or more and 1,000 or less, where a ratio (NCO / OH) of a mole amount of isocyanate groups of the di(tri)isocyanate (b1) to a total mole amount of hydroxyl groups of the polyol (b2) is 2 or more and 30 or less; and an isocyanurate group, where the average isocyanate functional group number is 5.1 or more and 7.0 or less, and the weight average molecular weight Mw is 4,000 or more and 43,000 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyisocyanate composition, a resin composition, a cured resin product, a cured resin film, an adhesive resin composition, and a surface protective film. [Background technology]

[0002] In recent years, there has been a demand for fast-drying, highly curable polyisocyanates amid labor shortages and the need to reduce energy consumption. At the same time, the structures of various highly functional devices, automobiles, and buildings are becoming more complex, and there is an increasing need for them to be applied to areas that require curved surfaces or stretching, so there is a demand for a combination of these. For example, flexible displays and foldable displays are examples of such displays, and the demand for these displays has been expanding rapidly in recent years. Accordingly, the demand for paints, plastics, adhesives, pressure sensitive adhesives, and surface protection films that can conform to curved surfaces is also expected to increase.

[0003] For example, Patent Document 1 discloses a pressure-sensitive adhesive composition that includes a (meth)acrylic polymer having a hydroxy group and an acid value of 0 mgKOH / g or more and less than 16 mgKOH / g, an alkylene oxide chain-containing (meth)acrylic oligomer having an acid value of 0.1 mgKOH / g or more and 40 mgKOH / g or less, a polyether-modified silicone having a reactive group, a polyisocyanate compound as a crosslinking agent, and an ionic compound. It is disclosed that the pressure-sensitive adhesive composition can provide a surface protection film for optical members that can simultaneously achieve high levels of antistatic properties and low contamination of adherends. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-128636 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, there is a demand for a pressure-sensitive adhesive composition that can provide a surface protection film that is more conformable to curved surfaces and unevenness, dries quickly, is easier to peel off, and causes less contamination of the adherend by the pressure-sensitive adhesive when peeled off than the technology described in Patent Document 1, etc.

[0006] The present invention has been made in consideration of the above circumstances, and provides a polyisocyanate composition that, when made into a surface protection film, has good application and peelability and is improved in terms of contamination by adhesives during peeling, as well as a resin composition, a cured resin product, a cured resin film, an adhesive resin composition, and a surface protection film each using the polyisocyanate composition. [Means for solving the problem]

[0007] That is, the present invention includes the following aspects. (1) A polyisocyanate composition comprising at least one di(tri)isocyanate (b1) selected from the group consisting of aliphatic di(tri)isocyanates and alicyclic di(tri)isocyanates, and a bifunctional or higher polyol (b2) having a number average molecular weight of 250 or more and 1000 or less, wherein the ratio NCO / OH of the molar amount of isocyanate groups in the di(tri)isocyanate (b1) to the total molar amount of hydroxyl groups in the polyol (b2) is 2 or more and 30 or less, the polyisocyanate composition contains isocyanurate groups, the average number of isocyanate functional groups is 5.1 or more and 7.0 or less, and the weight average molecular weight Mw is 4000 or more and 43000 or less. (2) The polyisocyanate composition according to (1), wherein the polyisocyanate has an isocyanate group content (NCO%) of 13.5% by mass or more and 18.3% by mass or less in a solvent-free state. (3) The polyisocyanate composition according to (1) or (2), wherein the polyisocyanate contains an allophanate group. (4) The polyisocyanate composition according to any one of (1) to (3), wherein the polyisocyanate contains an allophanate group and a urethane group. (5) The polyisocyanate composition according to any one of (1) to (4), wherein the polyol (b2) contains at least one polyester polyol. (6) The polyisocyanate composition according to any one of (1) to (5), wherein the polyol (b2) contains at least one polycaprolactone polyol. (7) The polyisocyanate composition according to any one of (1) to (6), wherein the polyol (b2) contains at least one kind of trifunctional or more and tetrafunctional or less polycaprolactone polyol. (8) A resin composition comprising the polyisocyanate composition according to any one of (1) to (7) and a crosslinkable functional group-containing compound. (9) The resin composition according to (8), wherein the crosslinkable functional group-containing compound contains a hydroxyl group, an epoxy group, an oxetane group, a carboxy group, an amino group, or a thiol group. (10) A resin cured product obtained by curing the resin composition according to (8) or (9) by light, electron beam, or heat. (11) A cured resin film comprising the cured resin according to (10), which has a Konig hardness of 20 to 150 cycles at 23° C. and a maximum stress of 10 MPa or more in a tensile test. (12) An adhesive resin composition comprising the polyisocyanate composition according to any one of (1) to (7) and a crosslinkable functional group-containing polymer, wherein the glass transition temperature Tg of the crosslinkable functional group-containing polymer is −75.0° C. or higher and 0.0° C. or lower, and the content of the polyisocyanate composition is 0.01 parts by mass or higher and 15.0 parts by mass or lower per 100 parts by mass of the crosslinkable functional group-containing polymer. (13) The pressure-sensitive adhesive resin composition according to (12), wherein the crosslinkable functional group-containing polymer is an acrylic polymer (A1) or a urethane polymer (A2) obtained by copolymerizing a crosslinkable functional group-containing monomer and a (meth)acrylic acid ester monomer having an ester group terminal carbon number of 1 or more and 18 or less. (14) The adhesive resin composition according to (13), wherein the content of the structural unit derived from the crosslinkable functional group-containing monomer is 0.01 mass% or more and 25 mass% or less relative to the total mass of the crosslinkable functional group-containing polymer. (15) The weight average molecular weight of the crosslinkable functional group-containing polymer is 2.0×10 5 More than 2.5 x 10 6 The adhesive resin composition according to any one of (12) to (14), which is: (16) The adhesive resin composition according to any one of (12) to (15), wherein the crosslinkable functional group-containing polymer contains at least one group selected from the group consisting of a hydroxyl group, an epoxy group, an oxetane group, a carboxy group, an amino group, and a thiol group. (17) A surface protection film comprising a plastic film and an adhesive layer on one or both sides of the plastic film, the adhesive layer being a cured product of the adhesive resin composition according to any one of (12) to (16). (18) The surface protective film according to (17), wherein the thickness of the adhesive layer is 1 μm or more and 1000 μm or less. (19) The surface protection film according to (17) or (18), in which the adhesive resin composition is applied onto a 38 μm-thick release-treated polyethylene terephthalate film, dried at 136° C. for 3 minutes to harden it, and then stored in an environment of 23° C. and 50% RH for 7 days. The adhesive layer having a thickness of 20 μm is peeled off from the release film, stored in an environment of 23° C. and 50% RH for 7 days, wrapped in a mesh sheet, immersed in ethyl acetate at 23° C. for 1 week, removed, and dried at 120° C. for 2 hours, and the gel fraction calculated by the above is 90.0% by mass or more and 100.0% by mass or less. (20) The adhesive resin composition was applied onto a 38 μm-thick release-treated polyethylene terephthalate film, dried at 136° C. for 3 minutes to harden it, and then stored in a 23° C., 50% RH environment for 7 days to form an adhesive layer having a thickness of 20 μm. The adhesive layer was then laminated to a thickness of 200 μm and cut to a width of 10 mm and a length of 40 mm. The adhesive layer peeled off from the release-treated polyethylene terephthalate film was set in a tensile tester with a chuck distance of 10 mm, and a Young's modulus in a tensile test performed at a speed of 300 mm / min in a 23° C. environment was 0.05 N / mm 2 More than 0.60N / mm 2 The surface protective film according to any one of (17) to (19) below: (21) The surface protection film according to any one of (17) to (20), wherein the adhesive resin composition is applied onto a polyethylene terephthalate film having a thickness of 25 μm, dried at 136° C. for 3 minutes to be cured, and then stored in an environment of 23° C. and 50% RH for 7 days, and the resulting surface protection film has an adhesive layer having a thickness of 20 μm, a width of 25 mm, and a length of 100 mm. The surface protection film is then attached to a glass substrate, pressed back and forth once with a 2 kg roller, and aged at 23° C. for 30 minutes, and the 180-degree peel adhesive strength measured at 23° C. and a speed of 300 mm / min is 0.02 N / 25 mm or more and 2.50 N / 25 mm or less. Effect of the Invention

[0008] According to this embodiment, a resin cured product having excellent quick-drying properties, hardness and strength, and a pressure-sensitive adhesive composition having excellent quick-drying properties and peelability can be obtained. When made into a surface protective film, the polyisocyanate composition has good conformability to curved surfaces and unevenness, good attachment and peelability, and improved contamination of an adherend by the pressure-sensitive adhesive during peeling, as well as a resin composition, a resin cured product, a resin cured film, a pressure-sensitive adhesive resin composition, and a surface protective film using the polyisocyanate composition can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment for carrying out the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. The present embodiment is an example for explaining the present invention, and the present invention is not limited to the present embodiment. The present invention can be carried out by appropriately modifying it within the scope of its gist.

[0010] The polyisocyanate composition of the present embodiment is preferably used for a resin composition, a resin cured product, a resin cured film, a coating composition, and an adhesive resin composition, which are excellent in quick drying. The most preferred embodiment is an adhesive resin composition for a surface protective film, which has good conformability to curved surfaces and unevenness, good quick drying properties, good attachment properties, and good peelability, and can provide a surface protective film with improved contamination of the adherend by the adhesive during peeling.

[0011] Prior to describing the polyisocyanate composition of the present embodiment, a crosslinkable functional group-containing polymer suitable for the adhesive resin composition will be described. The polyisocyanate composition is a polyisocyanate that serves as the crosslinking agent component (B) of the crosslinkable functional group-containing polymer.

[0012] <Crosslinkable functional group-containing polymer> The crosslinkable functional group-containing polymer may be any polymer containing a crosslinkable functional group capable of reacting with the isocyanate group of the polyisocyanate. The crosslinkable functional group is a functional group capable of forming a crosslinked structure with the crosslinking agent component (B), and specifically, for example, it is preferable to contain one or more selected from the group consisting of a hydroxyl group, an epoxy group, an oxetane group, a carboxy group, an amino group, or a thiol group, and among these, a hydroxyl group, an epoxy group, or a carboxy group is preferable, and a hydroxyl group is more preferable.

[0013] The crosslinkable functional group-containing polymer is obtained by polymerizing a crosslinkable functional group-containing monomer. The glass transition temperature Tg of the crosslinkable functional group-containing polymer is preferably −75.0° C. or more and 0.0° C. or less in the pressure-sensitive adhesive resin composition.

[0014] The content of the constitutional unit derived from the crosslinkable functional group-containing monomer is preferably 0.01% by mass or more and 25% by mass or less, more preferably 0.1% by mass or more and 20% by mass or less, even more preferably 0.5% by mass or more and 18% by mass or less, and particularly preferably 0.5% by mass or more and 17% by mass or less, based on the total mass of the crosslinkable functional group-containing polymer (A). When the content of the constitutional unit derived from the crosslinkable functional group-containing monomer is within the above numerical range, a surface protection film having good adhesion and peelability and improved contamination by the adhesive during peeling can be obtained. The content of the constitutional unit derived from the crosslinkable functional group-containing monomer can be calculated, for example, from the blending amount of the crosslinkable functional group-containing monomer used in the production of the crosslinkable functional group-containing polymer.

[0015] The crosslinkable functional group-containing polymer (A) is preferably an acrylic polymer (A1) obtained by copolymerizing a crosslinkable functional group-containing monomer with a (meth)acrylic acid ester monomer having an ester group terminal carbon number of 1 or more and 18 or less, and having a glass transition temperature Tg of -75.0°C or more and 0.0°C or less, or a urethane polymer (A2) having a glass transition temperature Tg of -75.0°C or more and 0.0°C or less.

[0016] The crosslinkable functional group-containing polymer (A) is more preferably an acrylic polymer (A1) obtained by copolymerizing a crosslinkable functional group-containing monomer and a (meth)acrylic acid ester monomer having an ester group terminal carbon number of 1 or more and 18 or less, and having a glass transition temperature Tg of -75.0°C or more and 0.0°C or less.

[0017] [Acrylic polymer (A1)] The acrylic polymer (A1) contains at least one polymerizable (meth)acrylic monomer unit having a crosslinkable functional group as the crosslinkable functional group-containing monomer unit. The crosslinkable functional group preferably contains a hydroxyl group, an epoxy group, an oxetane group, a carboxy group, an amino group, or a thiol group, more preferably contains a hydroxyl group, a carboxyl group, or an epoxy group, and even more preferably contains a hydroxyl group.

[0018] The acrylic polymer (A1) may contain a single crosslinkable functional group, or may contain two or more different types of crosslinkable functional groups in combination. That is, the acrylic polymer may be obtained by polymerizing a single polymerizable (meth)acrylic monomer having a crosslinkable functional group, or may be obtained by copolymerizing two or more polymerizable (meth)acrylic monomers having different types of crosslinkable functional groups.

[0019] The acrylic polymer (A1) preferably contains at least one (meth)acrylic acid ester monomer unit having an ester group terminal with 1 to 18 carbon atoms, in addition to the polymerizable (meth)acrylic monomer unit having a crosslinkable functional group. That is, the acrylic polymer (A1) may be obtained by copolymerizing one or more polymerizable (meth)acrylic monomers having a crosslinkable functional group and one or more (meth)acrylic acid ester monomers having an ester group terminal carbon number of 1 to 18. The (meth)acrylic acid ester monomer may or may not have a crosslinkable functional group, but it is preferable that it does not have one.

[0020] The number of carbon atoms at the terminal ester group of the (meth)acrylic acid ester monomer is preferably 1 or more and 18 or less.

[0021] Examples of the polymerizable (meth)acrylic monomer having a crosslinkable functional group include the following (i) to (v). These may be used alone or in combination of two or more. (i) Acrylic esters having a hydroxyl group, such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxybutyl acrylate, 4-hydroxybutyl acrylate, 6-hydroxyhexyl acrylate, and 8-hydroxyoctyl acrylate. (ii) Methacrylates having a hydroxyl group, such as 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 4-hydroxybutyl methacrylate, 6-hydroxyhexyl methacrylate, and 8-hydroxyoctyl methacrylate. (iii) (meth)acrylic acid esters having a polyvalent hydroxy group, such as acrylic acid monoester or methacrylic acid monoester of glycerin, and acrylic acid monoester or methacrylic acid monoester of trimethylolpropane. (iv) Unsaturated carboxylic acids such as acrylic acid and methacrylic acid. (v) (meth)acrylic acid esters having an epoxy group, such as glycidyl methacrylate.

[0022] Examples of the (meth)acrylic acid ester monomer having an ester group terminal carbon number of 1 or more and 18 or less include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, Examples of (meth)acrylic acid esters include nonyl acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate (lauryl (meth)acrylate), tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, benzyl (meth)acrylate, and cyclohexyl (meth)acrylate. These may be used alone or in combination of two or more.

[0023] The acrylic polymer (A1) may further contain, in addition to the polymerizable (meth)acrylic monomer unit having a crosslinkable functional group, other monomer units other than the above-mentioned (meth)acrylic acid ester monomers. That is, the acrylic polymer (A1) is obtained by polymerizing a polymerizable (meth)acrylic monomer having one or more crosslinkable functional groups, or by copolymerizing a polymerizable (meth)acrylic monomer having one or more crosslinkable functional groups with one or more other monomers. The other monomers may or may not have a crosslinkable functional group, but preferably do not have a crosslinkable functional group.

[0024] Examples of the other monomers include the following (i) to (ii). These may be used alone or in combination of two or more. (i) Unsaturated amides such as (meth)acrylamide, N-methylol acrylamide, diacetone acrylamide, and dimethylaminopropyl acrylamide. (ii) Styrene, vinyl toluene, vinyl acetate, (meth)acrylonitrile, N-vinylpyrrolidone, N-vinylcaprolactam, acryloylmorpholine, dimethylaminoethyl (meth)acrylate, and diethylaminoethyl (meth)acrylate.

[0025] Furthermore, as other monomers copolymerizable with the polymerizable (meth)acrylic monomer having a crosslinkable functional group, polymerizable ultraviolet-stable monomers disclosed in JP-A-1-261409 (Reference 1) and JP-A-3-006273 (Reference 2) may be used. Specific examples of the polymerizable ultraviolet-stable monomer include 4-(meth)acryloyloxy-2,2,6,6-tetramethylpiperidine, 4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 1-crotonoyl-4-crotonoyloxy-2,2,6,6-tetramethylpiperidine, and 2-hydroxy-4-(3-methacryloxy-2-hydroxypropoxy)benzophenone.

[0026] For example, the above-mentioned monomer components are solution-polymerized in the presence of a known radical polymerization initiator such as a peroxide or an azo compound, and the solution is diluted with an organic solvent, etc., as necessary, to obtain an acrylic polymer. When obtaining a water-based acrylic polymer, it can be produced by a known method such as a method of solution polymerization of an olefinically unsaturated compound and converting it into an aqueous phase, emulsion polymerization, etc. In this case, water solubility or water dispersibility can be imparted by neutralizing the acidic moiety of a carboxylic acid-containing monomer such as acrylic acid or methacrylic acid, or a sulfonic acid-containing monomer, etc., with an amine or ammonia.

[0027] The weight average molecular weight Mw(A) of the crosslinkable functional group-containing polymer (A) is 2.0×10 5 More than 2.5 x 10 6 It is preferable that the value is less than 3.0×10 5 Above 2.0×10 6 More preferably, it is 3.5×10 or less. 5 More than 1.8 x 10 6 More preferably, it is 3.7×10 5 More than 1.5 x 10 6 It is particularly preferable that the weight average molecular weight of the crosslinkable functional group-containing polymer (A) is within the above range, so that a surface protection film having good wettability, good adhesion, easy peeling, and improved contamination caused by the adhesive during peeling can be obtained. The weight average molecular weight Mw of the crosslinkable functional group-containing polymer (A) can be measured, for example, by the method described in the examples described later.

[0028] <Polyisocyanate composition> The polyisocyanate composition of the present embodiment is a polyisocyanate derived from at least one di(tri)isocyanate (b1) selected from the group consisting of aliphatic di(tri)isocyanates and alicyclic di(tri)isocyanates, and a bifunctional or higher polyol (b2) having a number average molecular weight of 250 or more and 1000 or less, wherein the ratio NCO / OH of the molar amount of isocyanate groups of the di(tri)isocyanate (b1) to the total molar amount of hydroxyl groups of the polyol (b2) is 2 or more and 30 or less, contains isocyanurate groups, has an average number of isocyanate functional groups of 5.1 or more and 7.0 or less, and has a weight average molecular weight Mw of 4000 or more and 43000 or less.

[0029] The di(tri)isocyanate is at least one selected from the group consisting of diisocyanates and triisocyanates. The polyisocyanate derived from an aliphatic or alicyclic di(tri)isocyanate (b1) and a di- or higher functional polyol (b2) is an aliphatic or alicyclic polyisocyanate.

[0030] The weight average molecular weight Mw(b) of the aliphatic or alicyclic polyisocyanate is 4000 or more and 43000 or less, preferably 4400 or more and 43000 or less, more preferably 4500 or more and 42000 or less, even more preferably 4500 or more and 40000 or less, even more preferably 4500 or more and 35000 or less, even more preferably 4500 or more and 32000 or less, even more preferably 4500 or more and 28000 or less, even more preferably 4500 or more and 23000 or less, even more preferably 4500 or more and 20000 or less, even more preferably 4500 or more and 18000 or less, and particularly preferably 4500 or more and 16000 or less. When the weight average molecular weight Mw(b) of the aliphatic or alicyclic polyisocyanate is within the above-mentioned numerical range, a surface protection film can be obtained which has an adhesive layer having good storage stability and wettability of the polyisocyanate, good adhesion, excellent quick-drying properties, curing properties, and application properties, excellent conformability to irregularities, is easier to peel off, and has improved contamination resistance. The Mw(b) of an aliphatic or alicyclic polyisocyanate is the weight average molecular weight based on polystyrene as determined by GPC measurement.

[0031] The average number of isocyanate functional groups of the aliphatic or alicyclic polyisocyanate (also referred to as the "average number of isocyanate groups") is 5.1 to 7.0, more preferably 5.1 to 6.9, more preferably 5.1 to 6.8, more preferably 5.1 to 6.7, particularly preferably 5.2 to 6.6, and most preferably 5.5 to 6.6. When the average number of isocyanate groups of the aliphatic or alicyclic polyisocyanate is within the above numerical range, a surface protection film having an adhesive layer with good wettability, good adhesion, excellent quick-drying properties, curing properties, and application properties, easier peeling, and improved contamination properties can be obtained.

[0032] The average number (fn) of isocyanate groups of an aliphatic or alicyclic polyisocyanate can be calculated using the following formula. In the formula, "Mn" indicates the number average molecular weight of the aliphatic or alicyclic polyisocyanate, and "NCO%" indicates the isocyanate group content of the aliphatic or alicyclic polyisocyanate. The number average molecular weight Mn of the aliphatic or alicyclic polyisocyanate is the weight average molecular weight based on polystyrene measured by GPC. The method for measuring NCO% will be described later.

[0033] [fn] = [Mn] × [NCO%] / 4200

[0034] The ratio NCO / OH of the molar amount of isocyanate groups in the di(tri)isocyanate (b1) to the total molar amount of hydroxyl groups in the polyol (b2) is preferably from 2 to 30, more preferably from 3 to 28, even more preferably from 4 to 27, and particularly preferably from 5 to 25. When the NCO / OH is within the above numerical range, a surface protective film having an adhesive layer with good wettability, good adhesion, excellent quick-drying properties, curing properties, and application properties, easier peeling properties, and improved contamination properties can be obtained.

[0035] The aliphatic or alicyclic polyisocyanate may have at least one structure selected from the group consisting of an allophanate structure, a uretdione structure, an iminooxadiazinedione structure, an isocyanurate structure, a urea structure, a urethane structure, and a biuret structure. Among these, it is preferable that the polyisocyanate has at least one structure selected from the group consisting of a urethane structure, an allophanate structure, a biuret structure, a urea structure, and an isocyanurate group.

[0036] The polyisocyanate contains an isocyanurate group. The polyisocyanate further contains an allophanate group, and more preferably contains an allophanate group and a urethane group.

[0037] [Di(tri)isocyanate (b1)] The di(tri)isocyanate (b1) is at least one selected from the group consisting of aliphatic di(tri)isocyanates and alicyclic di(tri)isocyanates, and preferably includes at least one selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates. The di(tri)isocyanate (b1) is used as an isocyanate monomer in the production of polyisocyanates.

[0038] Examples of aliphatic diisocyanates include, but are not limited to, 1,4-diisocyanatobutane, 1,5-diisocyanatopentane (hereinafter sometimes abbreviated as "PDI"), ethyl (2,6-diisocyanato)hexanoate, 1,6-diisocyanatohexane (hereinafter sometimes abbreviated as "HDI"), 1,7-diisocyanatoheptane, 1,8-diisocyanatooctane, 1,9-diisocyanatononane, 1,12-diisocyanatododecane, 2,2,4- or 2,4,4-trimethyl-1,6-diisocyanatohexane, etc. These aliphatic diisocyanates may be used alone or in combination of two or more.

[0039] Examples of alicyclic diisocyanates include, but are not limited to, 1,3- or 1,4-bis(isocyanatomethyl)cyclohexane (hereinafter sometimes abbreviated as "hydrogenated XDI"), 1,3- or 1,4-diisocyanatocyclohexane, 3,5,5-trimethyl-1-isocyanato-3-(isocyanatomethyl)cyclohexane (hereinafter sometimes abbreviated as "IPDI"), 4-4'-diisocyanato-dicyclohexylmethane (hereinafter sometimes abbreviated as "hydrogenated MDI"), 2,5- or 2,6-diisocyanatomethylnorbornane, etc. These alicyclic diisocyanates may be used alone or in combination of two or more.

[0040] These aliphatic diisocyanates and alicyclic diisocyanates may be used alone, or two or more of them may be used in combination. From the viewpoint of flexibility, the mass ratio of the alicyclic polyisocyanate to the aliphatic diisocyanate is preferably 0 / 100 or more and 30 / 70 or less.

[0041] Among these, the diisocyanate is preferably HDI, 1,4-diisocyanatobutane, PDI, 1,7-diisocyanatoheptane, 1,8-diisocyanatooctane, IPDI, hydrogenated XDI, or hydrogenated MDI, more preferably PDI, HDI, or IPDI, and further preferably PDI or HDI.

[0042] In the production of polyisocyanates, in addition to the diisocyanates described above, isocyanate monomers such as those shown below may be further used. (1) Aromatic diisocyanates such as diphenylmethane-4,4'-diisocyanate (MDI), 1,5-naphthalene diisocyanate, tolylene diisocyanate (TDI), xylylene diisocyanate, and m-tetramethylxylylene diisocyanate (TMXDI). (2) Triisocyanates such as 4-isocyanatomethyl-1,8-octamethylene diisocyanate (hereinafter sometimes referred to as "NTI"), 1,3,6-hexamethylene triisocyanate (hereinafter sometimes referred to as "HTI"), bis(2-isocyanatoethyl) 2-isocyanatoglutarate (hereinafter sometimes referred to as "GTI"), and lysine triisocyanate (hereinafter sometimes referred to as "LTI").

[0043] [Polyol (b2)] The polyol (b2) is a bifunctional or higher polyol (b2). The number average molecular weight of the polyol (b2) is 250 or more and 1000 or less, preferably 250 or more and 900 or less, more preferably 250 or more and 860 or less, more preferably 270 or more and 860 or less, and most preferably 270 or more and 550 or less.

[0044] The polyol (b2) is preferably at least one trifunctional polyol (triol) selected from the group consisting of polyester polyols, polyether polyols, epoxy polyols, polyolefin polyols, and polycarbonate polyols, more preferably contains at least one polyester polyol, more preferably is at least one polycaprolactone polyol, even more preferably is a trifunctional polyester polyol, and most preferably is a trifunctional polycaprolactone polyol.

[0045] Examples of bifunctional polyester polyols include the following polyester polyols (1) and (2). (1) Polyester polyols obtained by the condensation reaction of a dibasic acid, or a mixture of two or more kinds, with a dihydric alcohol, or a mixture of two or more kinds. (2) Polycaprolactone polyol obtained by ring-opening polymerization of ε-caprolactone with a dihydric alcohol. Examples of the dibasic acid include carboxylic acids such as succinic acid, adipic acid, dimer acid, maleic anhydride, phthalic anhydride, isophthalic acid, terephthalic acid, and 1,4-cyclohexanedicarboxylic acid. Examples of the dihydric alcohol include ethylene glycol, propylene glycol, diethylene glycol, 1,4-butanediol, neopentyl glycol, 1,6-hexanediol, trimethylpentanediol, and cyclohexanediol. Among these, as the difunctional polyester polyol, a difunctional polycaprolactone polyol is preferable.

[0046] The polyol (b2) is preferably a polyol with three or more functionalities, more preferably a polyol with three to ten functionalities, more preferably a polyol with three to seven functionalities, even more preferably a polyol with three to five functionalities, particularly preferably a polyol with three to four functionalities, and most preferably a trifunctional polyol (triol).

[0047] The trifunctional polyol (triol) is preferably at least one trifunctional polyol (triol) selected from the group consisting of polyester polyols, polyether polyols, epoxy polyols, polyolefin polyols, and polycarbonate polyols, more preferably a trifunctional polyether polyol or polyester polyol, and even more preferably a trifunctional polyester polyol.

[0048] Examples of trifunctional polyester polyols include the following polyester polyols (1) and (2). (1) Polyester polyols obtained by the condensation reaction of a dibasic acid, either alone or in a mixture of two or more kinds, with a trihydric alcohol, either alone or in a mixture of two or more kinds. (2) Polycaprolactone polyol obtained by ring-opening polymerization of ε-caprolactone with a trihydric alcohol. Examples of the dibasic acid include carboxylic acids such as succinic acid, adipic acid, dimer acid, maleic anhydride, phthalic anhydride, isophthalic acid, terephthalic acid, and 1,4-cyclohexanedicarboxylic acid. Examples of the trihydric alcohol include trimethylolpropane, glycerin, pentaerythritol, 2-methylolpropanediol, and ethoxylated trimethylolpropane. Among them, as the trifunctional polyester polyol, a trifunctional polycaprolactone polyol is preferable.

[0049] Examples of commercially available trifunctional polycaprolactone polyols include those available under the trade names "PLACCEL 303" (number average molecular weight 310), "PLACCEL 305" (number average molecular weight 550), "PLACCEL 308" (number average molecular weight 850), "PLACCEL 312" (number average molecular weight 1250), and "PLACCEL 320" (number average molecular weight 2000), all manufactured by Daicel Corporation; OD-X-2733 (number average molecular weight 300), OD-X-2735 (number average molecular weight 550), and OD-X-2742C (number average molecular weight 850), all manufactured by DIC Corporation.

[0050] The di- or higher functional polyol (b2) preferably contains at least one type of polycaprolactone polyol, and even more preferably contains at least one type of tri- or more-tetrafunctional polycaprolactone polyol. A trifunctional or more and tetrafunctional or less polycaprolactone polyol can be obtained, for example, by ring-opening polymerization of ε-caprolactone with a trivalent or more and tetravalent or less alcohol.

[0051] [Method for producing polyisocyanate composition] The aliphatic or alicyclic polyisocyanate can be obtained by reacting the above diisocyanate (b1) with a polyol (b2).

[0052] [Physical properties of polyisocyanate] The isocyanate group content (NCO group content) of the polyisocyanate composition, in a state (mass %) substantially not containing a solvent or di(tri)isocyanate, is preferably 13.0% or more and 18.3% or less, more preferably 13.5% or more and 18.2% or less, more preferably 13.7% or more and 18.0% or less, more preferably 13.7% or more and 18.0% or less, more preferably 14.0% or more and 18.0% or less, more preferably 14.5% or more and 18.0% or less, more preferably 14.8% or more and 18.0% or less, and particularly preferably 15.0% or more and 17.9% or less.

[0053] The NCO group content can be determined, for example, by reacting the isocyanate groups in the polyisocyanate composition with an excess of an amine (such as dibutylamine) and back-titrating the remaining amine with an acid such as hydrochloric acid.

[0054] The polyisocyanate preferably has an isocyanate group content (NCO%) of 13.0% or more and 18.3% or less, and more preferably 13.5% or more and 18.3% or less, in a state in which the solvent is removed.

[0055] <Resin composition> The resin composition of the present embodiment contains the above-mentioned polyisocyanate composition and a crosslinkable functional group-containing compound. The crosslinkable functional group-containing compound preferably contains a hydroxyl group, an epoxy group, an oxetane group, a carboxy group, an amino group, or a thiol group. The resin composition of the present embodiment can be cured by light, electron beams, or heat to obtain a cured resin. Examples of light include ultraviolet light and visible light.

[0056] <Cured resin product and cured resin film> The resin cured product can be obtained by applying the resin composition to a substrate and curing it. The thickness of the obtained cured resin film can be appropriately determined depending on the application, but is preferably 1 μm or more and 1000 μm or less, more preferably 2 μm or more and 900 μm or less, even more preferably 3 μm or more and 800 μm or less, preferably 4 μm or more and 700 μm or less, more preferably 4 μm or more and 600 μm or less, more preferably 4 μm or more and 500 μm or less, more preferably 4 μm or more and 400 μm or less, more preferably 4 μm or more and 300 μm or less, more preferably 4 μm or more and 200 μm or less, more preferably 4 μm or more and 100 μm or less, and most preferably 4 μm or more and 50 μm or less.

[0057] The above-mentioned polyisocyanate and crosslinkable functional group-containing compound are applied onto glass, and the cured film is preferably a resin cured film having a thickness of 50 μm and a Konig hardness of 20 to 150 times at 23° C. after storage for 168 hours at 23° C. and 65% RH. The Konig hardness is equal to or less than the upper limit and equal to or more than the lower limit, so that the resin cured film has appropriate hardness, strength, and flexibility and is excellent in curability. The resin cured film preferably has a maximum stress of 10 MPa or more in a tensile test.

[0058] <Adhesive resin composition> The adhesive resin composition of the present embodiment contains the above-mentioned polyisocyanate composition and a crosslinkable functional group-containing polymer having a glass transition temperature Tg of -75.0°C or more and 0.0°C or less. The content of the polyisocyanate composition is preferably 0.01 parts by mass or more and 15.0 parts by mass or less with respect to 100 parts by mass of the crosslinkable functional group-containing polymer. The adhesive resin composition is suitable as an adhesive resin composition for a surface protective film.

[0059] [Isocyanate group / Crosslinkable functional group] The molar ratio of the isocyanate group of the crosslinking agent component (B) to the crosslinkable functional group (particularly, hydroxyl group) of the crosslinkable functional group-containing polymer (A) contained in the adhesive resin composition for surface protection film of this embodiment (the molar ratio of isocyanate group / crosslinkable functional group) is determined based on the physical properties of the required surface protection film, but is usually 0.005 or more and 50 or less.

[0060] <Other ingredients> The adhesive resin composition for a surface protective film of this embodiment may further contain other additives. Examples of other additives include curing agents other than the crosslinking agent component (B) capable of reacting with the crosslinkable functional group-containing polymer (A), curing catalysts, solvents, pigments (extender pigments, coloring pigments, metallic pigments, etc.), tackifying resins, photopolymerization initiators, ultraviolet absorbers, light stabilizers, radical stabilizers, yellowing inhibitors that suppress coloring during the baking process, coating surface adjusters, flow adjusters, pigment dispersants, defoamers, thickeners and film-forming assistants, antistatic agents, etc.

[0061] Examples of the curing agent include melamine resins, urea resins, epoxy group-containing compounds or resins, carboxy group-containing compounds or resins, acid anhydrides, alkoxysilane group-containing compounds or resins, and hydrazide compounds. The curing catalyst may be a basic compound or a Lewis acid compound. Examples of the basic compound include metal hydroxides, metal alkoxides, metal carboxylates, metal acetylacetinates, hydroxides of onium salts, onium carboxylates, halides of onium salts, metal salts of active methylene compounds, onium salts of active methylene compounds, aminosilanes, amines, phosphines, etc. As the onium salts, ammonium salts, phosphonium salts, or sulfonium salts are preferable. Examples of the Lewis acid compound include an organotin compound, an organozinc compound, an organotitanium compound, and an organozirconium compound.

[0062] Examples of the solvent include 1-methylpyrrolidone, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, dipropylene glycol monomethyl ether, propylene glycol monomethyl ether, 3-methoxy-3-methyl-1-butanol, ethylene glycol diethyl ether, diethylene glycol diethyl ether, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dipropylene glycol dimethyl ether (DPDM), propylene glycol dimethyl ether, methyl ethyl ketone, acetone, and the like. Examples of the solvent include methyl isobutyl ketone, propylene glycol monomethyl ether acetate, ethanol, methanol, iso-propanol, 1-propanol, iso-butanol, 1-butanol, tert-butanol, 2-ethylhexanol, cyclohexanol, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, ethyl acetate, isopropyl acetate, butyl acetate, toluene, xylene, pentane, iso-pentane, hexane, iso-hexane, cyclohexane, solvent naphtha, mineral spirits, etc. These solvents may be used alone or in combination of two or more.

[0063] In addition, known pigments (extender pigments, colored pigments, metallic pigments, etc.), ultraviolet absorbers, light stabilizers, radical stabilizers, yellowing inhibitors that suppress coloring during the baking process, coating surface conditioners, flow conditioners, pigment dispersants, defoamers, thickeners, and film-forming aids can be appropriately selected and used.

[0064] The antistatic agent is preferably an alkali metal salt. Examples of the alkali metal salt include metal salts of lithium, sodium, and potassium. Specifically, for example, Li + , Na + , K + and a cation consisting of Cl - , Br - , I- , BF4 - , PF6 - , SCN - , ClO4 - , CF3SO3 - , (CF3SO2)2N - , (C2F5SO2)2N - , (CF3SO2)3C - Metal salts composed of anions consisting of the above are preferably used. Among them, lithium salts such as LiBr, LiI, LiBF4, LiPF6, LiSCN, LiClO4, LiCF3SO3, Li(CF3SO2)2N, Li(C2F5SO2)2N, and Li(CF3SO2)3C are particularly preferably used. These alkali metal salts may be used alone or in combination of two or more. In order to stabilize the ionic substance, a compound containing a polyoxyalkylene structure may be added.

[0065] <Method for producing adhesive resin composition for surface protective film> The adhesive resin composition for surface protection films can be produced by a conventional method, for example, a melt-kneading method using a general mixer such as a Banbury mixer, a single screw extruder, a twin screw extruder, a co-kneader, or a multi-screw extruder, or a method in which each component is dissolved or dispersed and mixed, then coated on a substrate film with a coater or the like, and the solvent is then removed by heating.

[0066] The adhesive resin composition for surface protection film of the present embodiment may be foamed in order to achieve the effects of weight reduction, flexibility, and improved adhesion. Foaming methods include chemical methods, physical methods, and the use of thermally expandable microballoons. In each case, air bubbles can be distributed inside the material by adding a chemical foaming agent such as an inorganic foaming agent or an organic foaming agent, or a physical foaming agent, or by adding a thermally expandable microballoon. In addition, hollow fillers (pre-expanded balloons) may be added to make the material lighter, more flexible, and more adhesive.

[0067] The adhesive resin composition for surface protective film of this embodiment may contain a tackifier resin to adjust adhesive strength and cohesive strength. Examples of the tackifier resin include rosin-based tackifier resins, terpene-based tackifier resins, petroleum-based tackifier resins, and styrene-based tackifier resins. These tackifier resins may be used alone or in combination of two or more. The softening point of the tackifier resin is preferably 90°C or higher and 160°C or lower.

[0068] <Surface protection film> The surface protection film of this embodiment includes a plastic film and an adhesive layer on one or both sides of the plastic film. The adhesive layer is made of a cured product of the adhesive resin composition for surface protection films described above.

[0069] In the surface protection film of this embodiment, the adhesive layer has good wettability, good adhesion, good conformability to irregularities, is easy to peel off, and has improved contamination caused by the adhesive when peeled off.

[0070] In the surface protection film of this embodiment, the thickness of the adhesive layer can be appropriately determined depending on the application, but is preferably 1 μm or more and 1000 μm or less, more preferably 2 μm or more and 900 μm or less, even more preferably 3 μm or more and 800 μm or less, more preferably 4 μm or more and 700 μm or less, more preferably 4 μm or more and 600 μm or less, more preferably 4 μm or more and 500 μm or less, more preferably 4 μm or more and 400 μm or less, more preferably 4 μm or more and 300 μm or less, more preferably 4 μm or more and 200 μm or less, more preferably 4 μm or more and 100 μm or less, and most preferably 4 μm or more and 50 μm or less.

[0071] The surface protective film of this embodiment can be produced, for example, by applying the adhesive resin composition for surface protective films onto a substrate, drying it as necessary, and then curing it.

[0072] Examples of the method for applying the adhesive resin composition for surface protective films to a substrate include a method of applying the composition using an applicator, a roll coater, a knife coater, a gravure coater, etc. When drying is performed after the application, examples of the method include a heat drying method in which the obtained laminate is placed in a dryer or the like and dried for 1 minute to 30 minutes at a temperature of 50° C. to 150° C. Other drying methods include, for example, natural drying, hot air drying, infrared drying, etc. The heating temperature during curing may be 70°C or higher and 160°C or lower, 75°C or higher and 155°C or lower, or 80°C or higher and 150°C or lower.

[0073] The adhesive layer for the surface protection film of this embodiment is preferably a gel fraction calculated by applying the adhesive resin composition for the surface protection film on a 38 μm-thick polyethylene terephthalate film that has been subjected to a release treatment, drying at 136 ° C for 3 minutes to harden it, storing the adhesive layer for 7 days at 23 ° C and 50% RH, peeling it off from the release film, wrapping it in a mesh sheet after storing it for 7 days at 23 ° C and 50% RH, immersing it in ethyl acetate at 23 ° C for 1 week, removing it, and drying it for 2 hours at 120 ° C. The gel fraction is preferably 90.0 mass % or more and 100.0 mass % or less. By having a gel fraction of the above lower limit or more, the curability, peelability, and adhesive residue are more excellent. The gel fraction referred to here is the percentage of the mass of the adhesive layer for the surface protection film after immersion in ethyl acetate and drying relative to the mass of the adhesive layer for the surface protection film before immersion in ethyl acetate.

[0074] The adhesive layer for the surface protection film of this embodiment is prepared by applying the adhesive resin composition for surface protection film to a 38 μm-thick release-treated polyethylene terephthalate film, drying and curing at 136° C. for 3 minutes, and then storing the resulting adhesive layer for 7 days in a 23° C., 50% RH environment to obtain an adhesive layer having a thickness of 200 μm. The adhesive layer is then cut to a width of 10 mm and a length of 40 mm. The adhesive layer peeled from the release-treated polyethylene terephthalate film is set in a tensile tester with a chuck distance of 10 mm, and a Young's modulus of 0.60 N / mm is obtained in a tensile test performed at a speed of 300 mm / min in a 23° C. environment. 2 It is preferable that the resistance is less than 0.55N / mm 2 More preferably, it is 0.50 N / mm 2 More preferably, it is 0.47 N / mm 2 When the Young's modulus is equal to or less than the above upper limit, the elastic modulus is lower, and the adhesiveness, wettability, and conformability to the adherend are more excellent. The lower limit of the Young's modulus is, for example, 0.05 N / mm 2 It can be said that:

[0075] The surface protection film of the present embodiment is prepared by applying the adhesive resin composition for surface protection film to a polyethylene terephthalate film having a thickness of 25 μm, drying and curing the composition at 136° C. for 3 minutes, and then storing the resulting surface protection film for 7 days under an environment of 23° C. and 50% RH. The resulting surface protection film is attached to glass as an adherend, pressed back and forth once with a 2 kg roller, and cured at 23° C. for 30 minutes. The 180-degree peel adhesive strength measured at 23° C. and a speed of 300 mm / min is preferably 0.01 N / 25 mm or more and 2.50 N / 25 mm or less, more preferably 0.02 N / 25 mm or more and 2.50 N / 25 mm or less, and more preferably 0.02 N / 25 mm or more and 2.50 N / 25 mm or less. / 25mm or more and 2.40N / 25mm or less, more preferably 0.025N / 25mm or more and 2.30N / 25mm or less, more preferably 0.030N / 25mm or more and 2.10N / 25mm or less, more preferably 0.030N / 25mm or more and 2.00N / 25mm or less, more preferably 0.030N / 25mm or more and 1.70N / 25mm or less, more preferably 0.030N / 25mm or more and 1.50N / 25mm or less, more preferably 0.030N / 25mm or more and 1.25N / 25mm or less, and most preferably 0.030N / 25mm or more and 1.00N / 25mm or less. When the 180-degree peel adhesive strength is within the above numerical range, the adhesiveness is good, the peeling is not too heavy, it is easy to peel off from the adherend, and the peelability can be made better.

[0076] As described above, the surface protection film of this embodiment has good curing properties, good wettability, good adhesion, is easy to peel off, and has improved contamination by the adhesive during peeling, and is therefore suitable for use, for example, as a surface protection film for optical components. EXAMPLES

[0077] The present invention will be described below with reference to examples, but the present invention is not limited to the following examples.

[0078] [Physical Properties 1] (glass transition temperature Tg) The glass transition temperature of the crosslinkable functional group-containing polymer (A) was determined by evaporating the organic solvent and water in a solution of the crosslinkable functional group-containing polymer (A) under reduced pressure, vacuum drying the polymer, and measuring the temperature at a heating rate of 5°C / min using a differential scanning calorimeter (DSC) measurement device.

[0079] [Physical Properties 2] (Number average molecular weight and weight average molecular weight) The number average molecular weight and weight average molecular weight are those measured by gel permeation chromatography (GPC) using the following apparatus, using polystyrene as a standard.

[0080] (Measurement conditions) Equipment: Tosoh Corporation, HLC-802A Column: Tosoh Corporation, G1000HXL x 1 G2000HXL x 1 G3000HXL x 1 Carrier: Tetrahydrofuran Detection method: Differential refractometer

[0081] [Physical Properties 3] (Isocyanate group content) First, 2 g to 3 g of the measurement sample was weighed out (Wg) in a flask. Then, 20 mL of toluene was added to dissolve the measurement sample. Then, 20 mL of a 2N toluene solution of di-n-butylamine was added, mixed, and left at room temperature for 15 minutes. Then, 70 mL of isopropyl alcohol was added and mixed. Then, this liquid was titrated with a 1N hydrochloric acid solution (factor F) as an indicator. The titration value obtained was V2 mL. Then, the titration value obtained without the sample was V1 ml. Then, the isocyanate group content (NCO%) (mass%) of the crosslinking agent component (B) was calculated from the following formula.

[0082] "Isocyanate group content (mass%)" = (V1-V2) x F x 42 / (W x 1000) x 100

[0083] [Physical Properties 4] (Average number of isocyanate functional groups) The average number of isocyanate functional groups (average NCO number) of the crosslinking agent component (B) was calculated by the following formula. In the formula, "Mn" means number average molecular weight, and the value measured in the above "Physical Properties 2" was used. "NCO%" was the value calculated in the above "Physical Properties 3".

[0084] "Average number of isocyanate functional groups" = (Mn x NCO% x 0.01) / 42

[0085] [Preparation of cured film of polyisocyanate composition (B) and crosslinkable functional group compound] The polyisocyanate composition (B) and an acrylic polyol (crosslinkable functional group compound) having a Tg of 15°C were mixed so that NCO / OH=1, and ethyl acetate was added to dilute the mixture to a concentration of 45%. The mixture was applied onto glass using an applicator, and after storing the mixture in an environment of 23°C and 65% RH for 168 hours, a cured film having a thickness of 50 μm was obtained.

[0086] [Evaluation of quick-drying property of resin composition containing polyisocyanate composition (B) and crosslinkable functional group compound] The polyisocyanate composition (B) and an acrylic polyol (crosslinkable functional group compound) with a Tg of 15°C were mixed to NCO / OH=1, and ethyl acetate was added to dilute the mixture to a concentration of 45%, which was then applied onto a release film using an applicator. After storing the mixture in an environment of 23°C and 50% RH for 24 hours, a cured film with a thickness of 50 μm was obtained. The gel fraction of the cured film was measured. Films with a gel fraction of 85% by mass or more were deemed to have good curability.

[0087] [Physical Properties 5] (Konig hardness) For each cured film, the Konig hardness (times) was measured in an environment of 23° C. using a Konig hardness tester (Pendulum hardness tester manufactured by BYK Gardner).

[0088] <Evaluation method> [Preparation of surface protection film 1 (adhesive layer)] Each adhesive resin composition for surface protection film was applied to a 38 μm-thick release-treated PET film with an applicator so that the thickness after drying was 20 μm, and then dried at 136° C. for 3 minutes. After that, it was stored in an environment of 23° C. and 50% RH for 7 days to obtain a surface protection film 1 (adhesive layer) for gel fraction measurement and tensile test. When measuring, the release-treated PET film was peeled off and the test was performed.

[0089] [Preparation of surface protection film 2] Each adhesive resin composition for surface protection films was applied onto a 25 μm thick polyethylene terephthalate (PET) film using an applicator so that the thickness after drying would be 20 μm, and then dried for 3 minutes at 136° C. Thereafter, the film was stored in an environment of 23° C. and 50% RH for 7 days to obtain surface protection film 2 for measuring 180° peel adhesive strength.

[0090] [Rating 1] (Gel fraction) The adhesive layer obtained in the above "Preparation of Surface Protection Film 1" was peeled off from the release film, and about 0.1 g to 0.2 g of the sample was collected, wrapped in a mesh sheet, immersed in ethyl acetate for one week, and then dried for two hours at 120° C. The gel fraction (mass%) was then calculated using the following formula. The curability was evaluated as good when the gel fraction was 90% by mass or more.

[0091] [Rating 2] (Tensile test: Young's modulus) The adhesive layer obtained in the above "Preparation of Surface Protection Film 1" was laminated to a thickness of 200 μm and cut to a width of 10 mm and a length of 40 mm. Then, only the adhesive layer peeled off from the release film was set in a tensile tester with a chuck distance of 10 mm, and the Young's modulus was measured at a speed of 300 mm / min using the tensile tester in an environment of 23°C. Young's modulus: 0.60N / mm 2 The following were evaluated as having good adhesion and conformability to the adherend.

[0092] [Rating 3] (180 degree peel adhesion and stain resistance) The surface protection film 2 obtained in the above "Preparation of surface protection film 2" was cut to a width of 25 mm and a length of 100 mm to obtain a test piece. The test piece was then attached to a glass substrate, and a 2 kg roller was rolled back and forth once to press the test piece onto the glass. After curing for 30 minutes at 23°C, the 180° peel adhesion was measured at a speed of 300 mm / min using a tensile tester. Those that were 0.02 N / 25 mm or more and 2.50 N / 25 mm were evaluated as having good adhesion and peelability.

[0093] Next, the surface of the adherend after measuring the 180° peel adhesive strength was visually observed and the stain resistance was evaluated according to the following evaluation criteria. (Evaluation Criteria) ○: No contamination (no visible adhesive remains on the glass surface) ×: Contamination occurred (adhesive remains visible on the glass surface)

[0094] <Synthesis of crosslinkable functional group-containing polymer (A)> [Synthesis Example 1-1] (Synthesis of Acrylic Polymer A-1) Into a four-neck flask equipped with a stirrer, a thermometer, a nitrogen gas inlet tube, and a cooling tube, 96 parts by mass of 2-ethylhexyl acrylate (2EHA) and 4 parts by mass of 4-hydroxybutyl acrylate (4HBA) were added, and 240 parts by mass of ethyl acetate was added as a solvent. Next, while stirring under a nitrogen gas atmosphere, 0.15 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) was added as a polymerization initiator, and the reaction was carried out at 67°C for 8 hours. After the reaction, the mixture was cooled to obtain an acrylic polymer A-1 with a solid content concentration of 30.0% by mass.

[0095] [Synthesis Examples 1-2 to 1-8] (Synthesis of Acrylic Polymers A-1 to A-8) Each acrylic polymer was synthesized in the same manner as in Synthesis Example 1-1, except that the blending ratio of each monomer was as shown in Table 1.

[0096] The compositions and physical properties of the synthesized acrylic polymers are shown in Table 1 below. In Table 1, the abbreviations of the monomers represent the following compounds. 4 ) is multiplied by 10 to the values ​​shown in Table 1. 4 This indicates that the value multiplied by Mw is equivalent to Mw.

[0097] (Crosslinkable Functional Group-Containing Monomer (a1)) 4HBA: 4-Hydroxybutyl acrylate HEA: Hydroxyethyl acrylate

[0098] ((Meth)acrylic acid ester monomer (a2)) 2EHA: 2-Ethylhexyl acrylate iOA: isooctyl acrylate iNA: Isononyl acrylate MA: Methyl acrylate BA: Butyl acrylate

[0099] [Table 1]

[0100] <Synthesis of polyisocyanate composition (B)> [Synthesis Example 2-1] (Synthesis of polyisocyanate component B-1) In a four-neck flask equipped with a thermometer, stirring blade, and reflux condenser, 100 parts by mass of HDI and 7.2 parts by mass of trifunctional polycaprolactone polyol (manufactured by Daicel Chemical Industries, Ltd., "Placcel 303" (trade name)) (equivalent amount of NCO / OH=17.1) were charged under a nitrogen gas flow, and the temperature inside the reactor was kept at 90°C for 2.0 hours while stirring to carry out a urethane reaction. Thereafter, the temperature inside the reactor was kept at 60°C, and an isocyanurate catalyst tetramethylammonium caprylate was added, and when the yield reached 50% by mass, phosphoric acid was added to stop the reaction. After filtering the reaction liquid, unreacted HDI was removed using a thin-film evaporator to obtain a polyisocyanate containing an isocyanurate group and an allophanate group. To 100 parts by weight of the obtained polyisocyanate, 0.91 parts by weight of polyester polyol (manufactured by Daicel Chemical Industries, Ltd., "Placcel 303" (trade name)) was added (an amount that would make the NCO% of the polyisocyanate 2 mol% relative to 100 mol%), and 0.01 parts by weight of 2-ethylhexyl acid phosphate (JP-508T, manufactured by Johoku Chemical Industry Co., Ltd.) was added, and the mixture was stirred at 95°C for 3.0 hours to obtain polyisocyanate component B-1 containing isocyanurate groups, allophanate groups, and urethane groups. The NCO content of polyisocyanate component B-1 was 17.8% by mass, the weight average molecular weight was 5950, and the average number of isocyanate functional groups was 5.69. In consideration of handling, ethyl acetate was added to obtain a polyisocyanate composition with a solid content of 70%.

[0101] [Synthesis Examples 2-2 to 2-7] (Synthesis of polyisocyanate components B-2 to B-7) Except for the types and blending ratios of raw materials as shown in Table 2, the same method as in Synthesis Example 2-1 was used to synthesize each polyisocyanate component.

[0102] [Synthesis Example 2-8] (Synthesis of polyisocyanate component B-8) A four-neck flask equipped with a thermometer, a stirring blade, and a reflux condenser was charged with 100 parts by mass of HDI and 8.9 parts by mass of trimethylolpropane (hereinafter sometimes referred to as "polyol b3'-1") under a nitrogen stream, and the temperature inside the reactor was maintained at 75°C for 5 hours with stirring to carry out a urethane reaction. The reaction liquid was filtered, and then unreacted HDI was removed using a thin-film evaporator to obtain a urethane-type polyisocyanate (hereinafter sometimes referred to as "polyisocyanate component B-8").

[0103] [Synthesis Example 2-9] (Synthesis of polyisocyanate component B-9) In a four-neck flask equipped with a thermometer, stirring blade, and reflux condenser, 100 parts by mass of HDI was charged under a nitrogen stream, and the temperature inside the reactor was maintained at 62°C while stirring. 0.095 parts by mass of trimethylbenzylammonium hydroxide was added and reacted for 4 hours. When the conversion rate reached 38% by mass, 0.02 parts by mass of phosphoric acid was added to stop the reaction. The reaction liquid was filtered, and unreacted HDI was removed using a thin-film evaporator to obtain an isocyanurate-type polyisocyanate (hereinafter, sometimes referred to as "polyisocyanate component B-9").

[0104] [Synthesis Example 2-10] (Synthesis of polyisocyanate component B-10) In a four-neck flask equipped with a thermometer, stirring blade, and reflux condenser, 100 parts by mass of HDI and 7.3 parts by mass of trifunctional polycaprolactone polyol (manufactured by DIC Corporation, "OD-X-2733" (trade name)) (equivalent amount of NCO / OH=17.2) were charged under a nitrogen gas flow, and the temperature inside the reactor was kept at 92°C for 2.0 hours while stirring to carry out a urethane reaction. Thereafter, the temperature inside the reactor was kept at 60°C, and an isocyanurate catalyst tetramethylammonium caprylate was added, and when the yield reached 50% by mass, phosphoric acid was added to stop the reaction. After filtering the reaction liquid, unreacted HDI was removed using a thin-film evaporator to obtain a polyisocyanate containing an isocyanurate group and an allophanate group. To 100 parts by weight of the obtained polyisocyanate, 0.91 parts by weight of polyester polyol (manufactured by DIC Corporation, "OD-X-2733" (trade name)) was added, and 0.01 parts by weight of 2-ethylhexyl acid phosphate (JP-508T, manufactured by Johoku Chemical Industry Co., Ltd.) was added, and the mixture was stirred at 95°C for 3.0 hours to obtain polyisocyanate component B-10 containing isocyanurate groups, allophanate groups, and urethane groups. The NCO content of polyisocyanate component B-1 was 17.7% by mass, the weight average molecular weight was 5980, and the average number of isocyanate functional groups was 5.71. In consideration of handling, ethyl acetate was added to obtain a polyisocyanate composition with a solid content of 70%.

[0105] [Synthesis Example 2-11] (Synthesis of polyisocyanate component B-11) In a four-neck flask equipped with a thermometer, a stirring blade, and a reflux condenser, 100 parts by mass of HDI and 12.0 parts by mass of a trifunctional polycaprolactone polyol (manufactured by Daicel Chemical Industries, Ltd., "Placcel 305" (trade name)) (equivalent amount of NCO / OH=18.2) were charged under a nitrogen gas flow, and the temperature inside the reactor was kept at 90°C for 2.0 hours while stirring to carry out a urethane reaction. Thereafter, the temperature inside the reactor was kept at 60°C, and an isocyanurate catalyst tetramethylammonium caprylate was added, and when the yield reached 50% by mass, phosphoric acid was added to stop the reaction. After filtering the reaction liquid, unreacted HDI was removed using a thin-film evaporator to obtain a polyisocyanate containing an isocyanurate group and an allophanate group. To 100 parts by weight of the obtained polyisocyanate, 1.68 parts by weight of polyester polyol (manufactured by Daicel Chemical Industries, "Placcel 305" (trade name)) was added, and 0.01 parts by weight of 2-ethylhexyl acid phosphate (JP-508T, manufactured by Johoku Chemical Industry Co., Ltd.) was added, and the mixture was stirred at 95°C for 3.0 hours to obtain polyisocyanate component B-11 containing isocyanurate groups, allophanate groups, and urethane groups. The NCO content of polyisocyanate component B-11 was 17.12% by mass, the weight average molecular weight was 7790, and the average number of isocyanate functional groups was 5.64. In consideration of handling, ethyl acetate was added to obtain a polyisocyanate composition with a solid content of 70%.

[0106] [Synthesis Example 2-12] (Synthesis of polyisocyanate component B-12) In a four-neck flask equipped with a thermometer, stirring blade, and reflux condenser, 100 parts by mass of HDI and 18.0 parts by mass of trifunctional polycaprolactone polyol (manufactured by Daicel Chemical Industries, Ltd., "Placcel 308" (trade name)) (NCO / OH=19 equivalent amount) were charged under a nitrogen gas flow, and the temperature inside the reactor was kept at 90°C for 2.0 hours while stirring to carry out a urethane reaction. Thereafter, the temperature inside the reactor was kept at 60°C, and an isocyanurate catalyst, tetramethylammonium caprylate, was added, and when the yield reached 50% by mass, phosphoric acid was added to stop the reaction. After filtering the reaction liquid, unreacted HDI was removed using a thin-film evaporator to obtain a polyisocyanate containing an isocyanurate group and an allophanate group. To 100 parts by weight of the obtained polyisocyanate, 2.57 parts by weight of polyester polyol (manufactured by Daicel Chemical Industries, "Placcel 308" (trade name)) was added, and 0.01 parts by weight of 2-ethylhexyl acid phosphate (JP-508T, manufactured by Johoku Chemical Industry Co., Ltd.) was added, and the mixture was stirred at 95°C for 3.0 hours to obtain polyisocyanate component B-12 containing isocyanurate groups, allophanate groups, and urethane groups. The NCO content of polyisocyanate component B-12 was 16.3% by mass, the weight average molecular weight was 8850, and the average number of isocyanate functional groups was 5.61. In consideration of handling, ethyl acetate was added to obtain a polyisocyanate composition with a solid content of 70%.

[0107] [Synthesis Example 2-13] (Synthesis of polyisocyanate component B-13) In a four-neck flask equipped with a thermometer, a stirring blade, and a reflux condenser, 68 parts by mass of HDI, 32 parts by mass of IPDI, and 3.24 parts by mass of trimethylolpropane (hereinafter sometimes referred to as "polyol b3'-1") were charged under a nitrogen gas flow, and the temperature inside the reactor was kept at 83°C for 1 hour under stirring to carry out a urethane reaction. Thereafter, an isocyanurate catalyst tetramethylammonium caprylate was added, and when the yield reached 43% by mass, phosphoric acid was added to stop the isocyanurate reaction. After further stirring at 88°C for 1.5 hours, the reaction liquid was filtered, and unreacted HDI and IPDI were removed using a thin-film evaporator to obtain an isocyanurate-type polyisocyanate (hereinafter sometimes referred to as "polyisocyanate B-13"). The NCO content of the obtained polyisocyanate B-13 was 18.8% by mass, the number average molecular weight was 3395, and the average number of isocyanate groups was 5.17. Taking handling into consideration, ethyl acetate was added to obtain a polyisocyanate composition with a solid content of 70%.

[0108] The compositions and properties of each synthesized polyisocyanate component are shown in Tables 2 and 3 below. 3 ) is multiplied by 10 to the values ​​shown in Tables 2 and 3. 3 The value multiplied by corresponds to Mw. In Tables 2 and 3, the polyols are the following compounds.

[0109] (Polyol (b2)) b2-1: Trifunctional polycaprolactone polyol, manufactured by Daicel Corporation, trade name "Placcel 303", number average molecular weight 310 b2-2: Trifunctional polycaprolactone polyol, manufactured by Daicel Corporation, trade name "Placcel 305", number average molecular weight 550 b2-3: Trifunctional polycaprolactone polyol, manufactured by Daicel Corporation, trade name "Placcel 308", number average molecular weight 850 b2-4: Trifunctional polycaprolactone polyol, OD-X-2733 manufactured by DIC, number average molecular weight 300

[0110] (Polyol (b3')) b3'-1: Trimethylolpropane (TMP)

[0111] [Table 2]

[0112] [Table 3]

[0113] <Evaluation of storage stability> The storage stability was evaluated according to the following criteria. ×: After the polyisocyanate was stored in a can filled with inert gas, gelation or viscosity increase rate was 3.0 times or more of the initial value after one year in an environment of 23°C. △: After the polyisocyanate is stored in a can filled with inert gas, the viscosity increase rate after one year in an environment of 23°C is 2.0 to less than 3.0 times the initial value. ◯: After the polyisocyanate is stored in a can filled with inert gas, the viscosity increase rate after one year in an environment of 23°C is 1.5 to less than 2.0 times the initial viscosity. ⊚: After the polyisocyanate is stored in a can filled with inert gas, the viscosity increase rate after one year in an environment of 23°C is less than 1.5 times the initial value.

[0114] <Production of Adhesive Resin Composition for Surface Protective Film> [Example 1] (Production of adhesive resin composition S-a1 for surface protective film) To 100 parts by mass of acrylic polymer A-1, 3.0 parts by mass of polyisocyanate component B-1, 0.1 parts by mass of dioctyltin dilaurate (DOT: Neostan 810 manufactured by Nitto Chemical Industry Co., Ltd.) as a crosslinking accelerator, and ethyl acetate were added to obtain an adhesive resin composition S-a1 for surface protection films with a solid content of 30% by mass.

[0115] [Examples 2 to 11 and Comparative Examples 1 to 4] (Production of Adhesive Resin Compositions S-a2 to S-a11 and S-b1 to S-b4 for Surface Protective Films) Each adhesive resin composition for surface protection films was produced using the same method as in Example 1, except that the types and blending ratios of the crosslinkable functional group-containing polymer (A) and the crosslinking agent component (B) were as shown in Tables 4 to 5.

[0116] Tables 4 and 5 show the compositions and evaluation results of each adhesive resin composition for surface protective films.

[0117] [Table 4]

[0118] [Table 5]

[0119] In Examples 1 to 11, cured resin products excellent in quick-drying properties, hardness and strength, and pressure-sensitive adhesive compositions excellent in quick-drying properties and peelability were obtained. When used as surface protection films, they had good adhesion and peelability, and the contamination caused by the pressure-sensitive adhesive during peeling was improved. In Comparative Examples 1 to 4, the crosslinking agent component (B) is poor in quick-drying property. In Comparative Example 2, the adhesive resin composition is poor in releasability and stain resistance. [Industrial Applicability]

[0120] According to the present embodiment, a resin cured product having excellent quick-drying properties, hardness and strength, and a pressure-sensitive adhesive composition having excellent quick-drying properties and peelability can be obtained. When made into a surface protective film, the polyisocyanate composition has good conformability to curved surfaces and unevenness, good attachment and peelability, and improved contamination of an adherend by the pressure-sensitive adhesive during peeling, as well as a resin composition, a resin cured product, a resin cured film, a pressure-sensitive adhesive resin composition, and a surface protective film using the polyisocyanate composition can be provided.

Claims

1. a polyisocyanate derived from at least one di(tri)isocyanate (b1) selected from the group consisting of aliphatic di(tri)isocyanates and alicyclic di(tri)isocyanates, and a di- or higher functional polyol (b2) having a number average molecular weight of 250 or more and 1,000 or less; the ratio NCO / OH of the molar amount of isocyanate groups of the di(tri)isocyanate (b1) to the total molar amount of hydroxyl groups of the polyol (b2) is 2 or more and 30 or less; Contains isocyanurate groups, The average number of isocyanate functional groups is 5.1 or more and 7.0 or less, The weight average molecular weight Mw is 4,000 or more and 43,000 or less. Polyisocyanate composition.

2. The polyisocyanate composition according to claim 1, wherein the polyisocyanate has an isocyanate group content (NCO%) of 13.5% by mass or more and 18.3% by mass or less in a solvent-free state.

3. 3. The polyisocyanate composition of claim 1 or 2, wherein the polyisocyanate contains allophanate groups.

4. 3. The polyisocyanate composition of claim 1, wherein the polyisocyanate contains allophanate groups and urethane groups.

5. 3. The polyisocyanate composition according to claim 1 or 2, wherein the polyol (b2) comprises at least one polyester polyol.

6. 3. The polyisocyanate composition according to claim 1 or 2, wherein the polyol (b2) comprises at least one polycaprolactone polyol.

7. The polyisocyanate composition according to claim 1 or 2, wherein the polyol (b2) comprises at least one trifunctional to tetrafunctional polycaprolactone polyol.

8. A resin composition comprising the polyisocyanate composition according to claim 1 or 2 and a crosslinkable functional group-containing compound.

9. The resin composition according to claim 8 , wherein the crosslinkable functional group-containing compound contains a hydroxyl group, an epoxy group, an oxetane group, a carboxy group, an amino group, or a thiol group.

10. A resin cured product obtained by curing the resin composition according to claim 8 with light, electron beams, or heat.

11. 11. A cured resin film comprising the cured resin according to claim 10, which has a Konig hardness of 20 to 150 cycles at 23° C. and a maximum stress of 10 MPa or more in a tensile test.

12. A pressure-sensitive adhesive resin composition comprising the polyisocyanate composition according to claim 1 or 2 and a crosslinkable functional group-containing polymer, The glass transition temperature Tg of the crosslinkable functional group-containing polymer is −75.0° C. or more and 0.0° C. or less, The adhesive resin composition has a content of the polyisocyanate composition of 0.01 parts by mass or more and 15.0 parts by mass or less relative to 100 parts by mass of the crosslinkable functional group-containing polymer.

13. The crosslinkable functional group-containing polymer An acrylic polymer (A1) obtained by copolymerizing a crosslinkable functional group-containing monomer and a (meth)acrylic acid ester monomer having an ester group terminal with 1 to 18 carbon atoms, or The adhesive resin composition according to claim 12, wherein the polymer (A2) is a urethane-based polymer.

14. The adhesive resin composition according to claim 13, wherein the content of the structural unit derived from the crosslinkable functional group-containing monomer is 0.01 mass% or more and 25 mass% or less with respect to the total mass of the crosslinkable functional group-containing polymer.

15. The weight average molecular weight of the crosslinkable functional group-containing polymer is 2.0×10 5 Above 2.5 x 10 6 The adhesive resin composition according to claim 12, wherein:

16. The adhesive resin composition according to claim 12, wherein the crosslinkable functional group-containing polymer contains at least one selected from the group consisting of a hydroxyl group, an epoxy group, an oxetane group, a carboxy group, an amino group, and a thiol group.

17. A plastic film; An adhesive layer is provided on one or both sides of the plastic film, A surface protection film, wherein the adhesive layer is a cured product of the adhesive resin composition according to claim 12.

18. The surface protective film according to claim 17 , wherein the adhesive layer has a thickness of 1 μm or more and 1000 μm or less.

19. The adhesive resin composition is applied onto a 38 μm-thick release-treated polyethylene terephthalate film, dried at 136° C. for 3 minutes to harden it, and then stored in an environment of 23° C. and 50% RH for 7 days. The adhesive layer having a thickness of 20 μm is peeled off from the release film, and after storing in an environment of 23° C. and 50% RH for 7 days, it is wrapped in a mesh sheet, immersed in ethyl acetate at 23° C. for 1 week, removed, and dried at 120° C. for 2 hours. The surface protection film described in claim 17 has a gel fraction calculated by: 90.0 mass% or more and 100.0 mass% or less.

20. The adhesive resin composition was applied onto a 38 μm-thick release-treated polyethylene terephthalate film, dried at 136° C. for 3 minutes to cure, and then stored in a 23° C., 50% RH environment for 7 days. The adhesive layer was laminated to a thickness of 200 μm and cut to a width of 10 mm and a length of 40 mm. The adhesive layer peeled from the release-treated polyethylene terephthalate film was set in a tensile tester with a chuck distance of 10 mm, and a Young's modulus of 0.05 N / mm was measured in a tensile test performed at a speed of 300 mm / min in a 23° C. environment. 2 0.60N / mm or more 2 The surface protective film according to claim 17, wherein:

21. The adhesive resin composition is applied onto a polyethylene terephthalate film having a thickness of 25 μm, dried at 136° C. for 3 minutes to harden it, and then stored in an environment of 23° C. and 50% RH for 7 days. The adhesive layer is then attached to a glass substrate, and pressed back and forth once with a 2 kg roller. After curing at 23° C. for 30 minutes, the 180-degree peel adhesive strength measured at 23° C. and a speed of 300 mm / min is 0.02 N / 25 mm or more and 2.50 N / 25 mm or less.

Citation Information

Patent Citations

  • Adhesive composition and optical member surface protective film

    JP2017128636A